2019
DOI: 10.3889/oamjms.2019.145
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Type of Cleft and Nasal Air Emission in Speech of Children with Cleft Palate or Cleft Lip and Palate

Abstract: BACKGROUND: Cleft palate, due to damage of the soft palate, leads to dysfunction, i.e., inappropriate closure of the velopharynx during speech production, thus resulting in velopharyngeal insufficiency which characterises with hypernasal speech and nasal air loss/emission during speech production. AIM: To establish the relationship between the type of cleft according to the Veau classification and the degree of nasal air emission in the speech of patients with cleft using auditory-visual perceptual asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…4,6,7,9,11,19,20 Although the details of this association remain unclear, it has been suggested that more extensive clefts are more difficult to repair because they involve a larger area of the palate, making complications more likely. 1,20 Taken with our finding of no substantial difference in fistula formation between palatoplasty procedures, these data reinforce the concept that other factors, such as Veau cleft type, primarily influence the likelihood of fistula development after primary palatoplasty. Adoption status was one of the demographic variables in our study that had a considerable effect on fistula formation.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…4,6,7,9,11,19,20 Although the details of this association remain unclear, it has been suggested that more extensive clefts are more difficult to repair because they involve a larger area of the palate, making complications more likely. 1,20 Taken with our finding of no substantial difference in fistula formation between palatoplasty procedures, these data reinforce the concept that other factors, such as Veau cleft type, primarily influence the likelihood of fistula development after primary palatoplasty. Adoption status was one of the demographic variables in our study that had a considerable effect on fistula formation.…”
Section: Discussionsupporting
confidence: 84%
“…Cleft palates occur secondary to incomplete closure of the velopharyngeal sphincter and impair many oral functions, including verbal communication and feeding. 1,2 The goal of primary palatoplasty is anatomical reconstruction of the palate to allow for normal speech and craniofacial development and function. 1,3,4 Various primary palatoplasty techniques exist, and there is little consensus over which operative method is superior.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These anomalies pose challenges for not only the patient and the family but also the therapeutic team due to the improper functioning of the craniofacial apparatus, which affects each element of the stomatognathic system. Specifically, a lack of developmental connection between the tissues of the lip, alveolar process, and potential oronasal fistula may affect such activities as sucking, swallowing, the expression of emotions, the formation of thoughts, and efficient communication [40][41][42]. Moreover, the impaired formation of negative intraoral pressure during sucking and swallowing in this disorder results in the impaired nutrition of the newborn and an unsatisfactory pace of weight gain [41].…”
Section: Orofacial Cleft-clinical Features and Manifestationsmentioning
confidence: 99%